The Balance Scorecard Practice and Performance in XY University - Anuforo, Peter U (2018)
The intensity of competition among contemporary Higher Education Institution (HEIs) has led to many of such institutions to focus more on how to provide high quality education so as to attain a suitable position in the university world ranking by adopting a suitable performance management. This study aims to demonstrate how XY University (XYU) implements and uses the BSC to enhance and improve its strategic plans. This study employed a qualitative case study approach. Data were collected using interviews and analysis of documents and were analyzed qualitatively using thematic analysis. Consistent with Kaplan and Norton (1992) BSC model in public sector, findings indicates that the case institution has implemented the BSC ideology within its unique context. The study found that in implementing the BSC project, the university staff’s buy-in, top management commitment, organizational culture and communication strategy is critical for its success. Also, findings revealed that the implementation of BSC ideology in XYU has improved its’ performance in that it helps to improve the case institution’s overall university rankings. The implementation of the BSC also helps the university’s management to monitor its performance. Future study should consider more institution that implements BSC so as to get more detail results that may be generalized.